The use of combined cognitive training and non-invasive brain stimulation to modulate impulsivity in adult populations: a systematic review and meta-analysis of existing studies - Najat R. Khalifa; Yousef Alabdulhadi; Pilar Vazquez; Charlotte Wun; Peng Zhang (Frontiers in Psychiatry, 2024)
IntroductionImpulsivity, a tendency to act rashly and without forethought, is a core feature of many mental disorders that has been implicated in suicidality and offending behaviours. While research supports the use of non-invasive brain stimulation (NIBS) techniques, such as transcranial direct current stimulation (tDCS), to modulate brain functions, no studies specifically reviewed the use of combined cognitive training and NIBS to modulate impulsivity.MethodsWe aimed to conduct a systematic review and meta-analysis to synthesise the literature on the use of combined cognitive training and NIBS to modulate impulsivity and its subdomains (motor, delay discounting, reflection). We searched Scopus, PsychInfo, Medline, and Cinahl electronic databases, dissertations database, and Google scholar up to September 2024.ResultsFollowing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, four randomised controlled studies involving the use of combined cognitive training and tDCS in 127 subjects were included in the study. These studies included subjects with substance use disorders, obesity, and Parkinson’s disease. Meta-analysis showed that combined cognitive training and tDCS had no statistically significant effects on motor impulsivity as measured using reaction times on the Stop Signal Task and Go/No Go tasks. One study that measured impulsiveness scores on a delay discounting task also showed no significant results. No studies measured reflection or cognitive impulsivity.DiscussionThere is a dearth of literature on the use of combined cognitive training and NIBS for impulsivity. This in conjunction of clinical heterogeneity across studies makes it difficult to draw definitive conclusions about the neuromodulation of impulsivity and its subdomains using combined cognitive training and NIBS. The findings of this study highlight the need to conduct more studies in the field.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD 42024511576.